Amil Professional Ethics in Zakat Management - Muhammad Miftahul Ikhsan; Hafidah Ulya Adila; Syahrul Anwar; Dede Kania (Yayasan Mentari Madani, 2023)
Zakat is giving some of the property owned by individuals and then must be issued and given to Muslims, one of which is given to underprivileged people. The government in this case helps increase the potential of zakat by forming an amil zakat agency. The tempting of zakat funds managed by many causes managers to become complacent. There are so many cases related to zakat management. This is what we must understand that as a profession amil zakat must have a strong determination to help others, not to enrich oneself. This type of research uses literature research that takes data through information by obtaining library materials, data techniques that have been obtained by reviewing and analyzing, both in the form of books, journals, research results. As well as by using descriptive analysis techniques. Yusuf Qardhawi said that amilin is a person who works as a zakat collector, both including those who collect, inform, calculate and distribute zakat. Professional ethics that should be applied from amil zakat are, Openness and Transparency, Integrity and Credibility, Professionalism, Fairness and distribution, Efficient operations, Empathetic approach